Analisis Kualitas Layanan dan Lokasi terhadap Kepuasan Pasien Post Partum Berimplikasi terhadap Loyalitas Pasien RSUD Majenang - Purnanda, Abiyyu (Journal of Comprehensive Science, 2024)
Post partum period (1 hour to 42 days after birth) is a crucial phase but often ignored, with the result that many maternal and infant deaths occurring during this period. WHO recommends antenatal care examinations at least three times after giving birth. Low-income countries has challenges in providing inadequate care, leading to high maternal and infant mortality rates. Evaluation of health service quality and strategic location is important to increase patient satisfaction and loyalty in RSUD Majenang as a strategic hospital in Cilacap. Aim: This study aims to determine and analyze health quality of service and hospital location (Access, place, infrastructure) on postpartum patient satisfaction which has implications for patient loyalty. Methods: This study uses quantitative approach with descriptive verification methods. Research sample obtained was 110 people based on the Slovin formula. Data collection uses a questionnaire and data analysis design with univariate, bivariate and multivariate analysis. Results: Univariate analysis show that service quality, patient satisfaction and patient loyalty are in the good category and the hospital location is in the very good category. Bivariate analysis shows that 2 variables obtained a significance value (p<0.05). Multivariate analysis also showed that more than 2 variables obtained a significance value (p<0.05). Conclusion: Health service quality and hospital location influence patient satisfaction which has implications for patient loyalty.